Nominal genera and species of Diptera misidentified as to family by A.Z. Lehrer (Diptera: Muscidae, Tachinidae) - Cerretti, P.; Morgulis, E.; Michelsen, V.; Pape, T. (Zootaxa, 2023)
Nominal genera and species misidentified to family by A.Z. Lehrer are revised and annotated, with habitus photographs given for all holotypes. New synonyms in the Muscidae: Dobrogiella Lehrer & Oprişan, 2013 = Pyrellia Robineau-Desvoidy, 1830, syn. nov., Dobrogiella phallogreciana Lehrer & Oprişan, 2013 = Pyrellia vivida Robineau-Desvoidy, 1830, syn. nov. New synonyms and new combinations in the Tachinidae: Benigramma Lehrer, 2013 = Thelairosoma Villeneuve, 1916, syn. nov., B. bellanda Lehrer, 2013 = Thelairosoma bellanda (Lehrer, 2013), comb. nov.; Eweka Lehrer, 2012 = Pales Robineau-Desvoidy, 1830, syn. nov., Eweka cordicerci Lehrer, 2012 = Ctenophorocera [now Pales] pauciseta Mesnil, 1950, syn. nov.; Mawuphalla Lehrer, 2013 = Ceracia Rondani, 1865, syn. nov., Mawuphalla antennomyia Lehrer, 2013 = Myothyria [now Ceracia] africana Mesnil, 1959, syn. nov.; Paraphalloides Lehrer, 2013 = Pales Robineau-Desvoidy, 1830, syn. nov., Paraphalloides epiphallops Lehrer, 2013 = Pales epiphallops (Lehrer, 2013), comb. nov.; Spinuphalla Lehrer, 2013 = Drino Robineau-Desvoidy, 1863, syn. nov., Spinuphalla juxtina Lehrer, 2013 = Drino (Palexorista Townsend, 1921) juxtina (Lehrer, 2013), comb. nov.